A prospective study to review the functional outcome between patellofemoral resurfacing versus non resurfacing in total knee replacement - Balemane, Sharat; Attar, Arshad; Dsouza, Aaron Ruben (International Journal of Research in Orthopaedics, 2018)
Background: A prospective study to review the functional outcome between patellofemoral resurfacing versus non resurfacing in posterior stabilized TKR. Methods: We studied a total of 63 patients with tricompartmental osteoarthritis of knee. These patients underwent total knee arthroplasty between April 2013 to September 2013 at Preethi hospital, Madurai. It was prospective study which was followed up for period of 1 year. There were two groups which were made randomly into patellofemoral resurfacing group (group A n=30) and the non resurfacing group (group B n=33). In the patellofemoral resurfacing group, patella was resurfaced with the help of cemented poly component and in the non-resurfacing group, the osteophytes of the patella was removed, it was reshaped to match the trochlea of the femoral prosthesis and circumpatellar denervation was done. Knee society score (KSS), anterior knee pain, knee society function score and patient satisfaction was compared between both the groups. Results: There was significant difference in anterior knee pain scale and incidence of anterior knee pain was less as compared in the resurfacing group. However 1 year of follow up of both groups concluded that there was no significant differences for functional outcomes. Patient satisfaction scale was significant in patellofemoral resurfacing group. Conclusions: Study showed that apart from significant improvement in anterior knee pain scale there was no significant difference for both groups after 1 year follow up in clinical outcome, except for patient satisfaction scale. For patellofemoral pain and severe patellofemoral arthritis it is recommended to perform patellar resurfacing, otherwise patellar resurfacing do not have any added advantage.